A Summer Nudge Campaign to Motivate Community College STEM Students to Reenroll - Ross E. O'Hara; Betsy Sparrow (SAGE Publishing, 2019)
Despite growing economic opportunities in "middle-skills" science, technology, engineering, and mathematics (STEM) professions, the majority of community college STEM students leaves the STEM pipeline or withdraws from college altogether. We tested an intervention that addressed one reason why students abandon STEM: psychosocial barriers, including identity threats, a lack of belonging, and a mismatch between students' values and those prevalent in STEM. Our intervention leveraged behavioral science ("nudging") strategies as part of a 7-week summer campaign to encourage reenrollment, delivered via text message to 1,367 randomly selected first-year students at three community colleges. The intervention increased overall fall reenrollment by 7 percentage points; the effect was primarily observed among STEM students (+10 percentage points) and students taking summer courses (+10 percentage points). Our results indicate that interventions that target psychosocial barriers experienced by community college STEM students can increase retention and should be considered alongside broader reforms.